2020
DOI: 10.1590/1984-3143-ar2019-0134
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression of interferon-stimulated genes and ubiquitin activating enzyme E1-like in ovine thymus during early pregnancy

Abstract: in expression of interferon-stimulated genes and ubiquitin activating enzyme E1-like in ovine thymus during early pregnancy. Anim Reprod. 2020;17(2):e20190134.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In animal studies, changes in the population of T lymphocytes mainly include an increase in the Th cell population during early pregnancy ( 149 ), a greater percentage of type 2 helper cells in relation to type 1 helper cells ( 148 , 164 ), changes in the toll-like receptor (TLR) expression within thymic epithelial cells, and the synthesis of prostaglandins and proteins stimulated by interferon ( 150 , 151 ). These changes are directly responsible for the phenomenon of fetal immunotolerance, inhibiting the development and activation of a subpopulation of T lymphocytes that can stimulate inflammatory reactions within the uterine endometrium, while maintaining the endometrial and trophoblast defense against pathogens ( 165 ).…”
Section: Thymusmentioning
confidence: 99%
“…In animal studies, changes in the population of T lymphocytes mainly include an increase in the Th cell population during early pregnancy ( 149 ), a greater percentage of type 2 helper cells in relation to type 1 helper cells ( 148 , 164 ), changes in the toll-like receptor (TLR) expression within thymic epithelial cells, and the synthesis of prostaglandins and proteins stimulated by interferon ( 150 , 151 ). These changes are directly responsible for the phenomenon of fetal immunotolerance, inhibiting the development and activation of a subpopulation of T lymphocytes that can stimulate inflammatory reactions within the uterine endometrium, while maintaining the endometrial and trophoblast defense against pathogens ( 165 ).…”
Section: Thymusmentioning
confidence: 99%
“…Extensive changes occur in gene expression of pregnant animals' cells, especially ISGs and immune response-related genes (Bauersachs et al, 2006;Walker et al, 2010). Pregnant ewes had a higher expression of ISGs in the thymus (Zhang et al, 2020), higher expression of IL5, and a lower expression of IFNG, IL2, IL4, IL6, and IL10 in the liver (Yang et al, 2019). The expression of anti-inflammatory factors, such as IL10 and transforming growth factor-beta (TGFB) and pro-inflammatory like TNFA, were reported in endometrial and immune cells in cows (Rashid et al, 2018;Shirasuna et al, 2012;Talukder et al, 2017).…”
Section: Immunological Changes During Maternal Recognition Of Pregnancymentioning
confidence: 99%
“…Successful pregnancy outcome is implicated in the regulation of maternal regulatory T cells at the maternal–fetal interface, and regulatory T cells are partly derived from the thymus, which improve maternal tolerance to the fetus in pregnancy 14 . It has been reported that early pregnancy affects expression of P4 receptor, P4-induced blocking factor, T-helper cytokines, prostaglandin synthases, melatonin receptors 1, cluster of differentiation 4 (CD4), gonadotropin releasing hormone and its receptor in the maternal thymus in sheep 7 , 15 18 . In addition, toll-like receptor pathway and complement system are involved in the immune regulation of the maternal thymus during early pregnancy in sheep 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%